Compiling an Arabic-English Transport Dictionary through Corpus Linguistic Methods - Maura Syafa’ah, Della; Hizbullah, Nur (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2023)
This research aims to compile an Arabic-English Transport Dictionary through Corpus Linguistic Methods. This dictionary is intended for general learners. Types of qualitative descriptive research and this research used a discourse analysis. This research used a discourse analysis of secondary data. The source of the data involved dictionary data from Arabic websites containing Arabic and English terms in the field of transportation, namely ootlah.com, and tostpost.com. The data collection technique was through discovering synonyms or similar Arabic and English words in the ootlah.com and tostpost.com. Then, collecting the terms related to transportation. After that, combine them into a table and sort by alphabetical letter. When the vocabulary has been combined, then eliminate the similar vocabulary and move it to the document work page according to the alphabet. The results obtained from this study revealed the vocabulary that was previously collected with a total of 600, then eliminated to around 460 Arabic vocabulary in the field of transportation, with eighteen different links from two websites of ootlah.com and tostpost.com produced by the author. In conclusion, the Arabic-English Transport Dictionary has been well arranged through Corpus Linguistics Methods.